THE UNITY OF CONTENT AND FORM IN STORIES - Kakharova Mohigul Yusufovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article analyzes the unity of content and form in Jack London‘s The Night-Born and Abdulla Qahhor‘s ―Radiant Peaks‖, focusing on how linguistic choices reflect and reinforce each story‘s central themes and character development. Although the protagonist‘s life is disrupted, the character's pursuit of happiness reflects an American national trait in ―The Night-Born‖. In ―Radiant Peaks‖, the treatment of a woman whose life has been ruined reflects an Uzbek national attitude, seeing her as a ―a divorced woman‖ The Uzbek national belief that parents should never have bad thoughts about their children: the old man and woman console themselves having positive thoughts about their daughter.